FREQUENCY OF BLOOD GROUPS AMONGA SAMPLE OF PATIENTSWITH RENAL FAILURE AT ROYAL MEDICAL SERVICES - Samar Younes Alhawary; Mais Elian Al-Abdallat; Samar Atallah Ahmad Alamro; Raada Jamal Saada; Abdelkhaleq Ahmad Mohammad Alshboul; Tamador Alsmadi; Jaafar Abu Abeeleh; Mahmoud Abu Abeeleh (European Scientific Journal, ESJ, 2015)
Introduction: Renal failure underlies various etiologies among which are infectious and autoimmune origins which may link directly or indirectly with blood groups. Objectives: To determine the frequency of blood groups among a sample of patients with renal failure at Royal medical services, and to investigate the association of renal function tests with blood groups. Methodology: A retrospective study design was followed to collect data from files of patients with renal failure. Files of renal patients was included if blood groups were written and kidney function tests were provided. A data sheet was made for each patient that included relevant information about renal patients. A total of 197 files were reviewed. Data were entered into excel sheet to make raw data for all patients. Data analysis was conducted using SPSS V20. Data were presented as frequencies and percentages. The relationships between blood groups and renal function tests were investigated using T-independent test. Significance was considered at alpha level < 0.05. Results: the most prevalent blood group among renal failure patients was blood group A (45.7%), blood group O (30.4%), blood group B (17.3%), and blood group AB (6.6%). When biochemical tests including renal function tests were compared between renal failure patients according their blood groups, results showed slight variations, which were not statistically significant (p>0.05), except for potassium level which was observed in its maximal level among patients with blood group A, and its minimal levels were observed among patients with blood group AB (p=0.032). Conclusions: The present study showed that renal failure patients exhibited more frequency with blood groups A and O and agreed with other studies in which blood group AB is the least associated blood group with renal failure. The level of potassium was highest in patients with blood group A and lowest in patients with blood group AB and this was statistically significant (p=0.032).